Microbiota composition and its impact on DNA methylation in colorectal cancer - Gutierrez-Angulo, Melva; Ayala-Madrigal, Maria de la Luz; Moreno-Ortiz, Jose Miguel; Peregrina-Sandoval, Jorge; Garcia-Ayala, Fernando Daniel (Frontiers in Genetics, 2023)
Colorectal cancer is a complex disease resulting from the interaction of genetics, epigenetics, and environmental factors. DNA methylation is frequently found in tumor suppressor genes to promote cancer development. Several factors are associated with changes in the DNA methylation pattern, and recently, the gastrointestinal microbiota could be associated with this epigenetic change. The predominant phyla in gut microbiota are Firmicutes and Bacteroidetes; however, an enrichment of Bacteroides fragilis, Fusobacterium nucleatum, and Streptococcus bovis, among others, has been reported in colorectal cancer, although the composition could be influenced by several factors, including diet, age, sex, and cancer stage. Fusobacterium nucleatum, a gram-negative anaerobic bacillus, is mainly associated with colorectal cancer patients positive for the CpG island methylator phenotype, although hypermethylation in genes such as MLH1, CDKN2A, MTSS1, RBM38, PKD1, PTPRT, and EYA4 has also been described. Moreover, Hungatella hathewayi, a gram-positive, rod-shaped bacterium, is related to hypermethylation in SOX11, THBD, SFRP2, GATA5, ESR1, EYA4, CDX2, and APC genes. The underlying epigenetic mechanism is unclear, although it could be implicated in the regulation of DNA methyltransferases, enzymes that catalyze the transfer of a methyl group on cytosine of CpG sites. Since DNA methylation is a reversible event, changes in gut microbiota could modulate the gene expression through DNA methylation and improve the colorectal cancer prognosis.